Evaluating a Moist Isentropic Framework for Poleward Moisture Transport: Implications for Water Isotopes Over Antarctica. Issue 13 (10th July 2019) - Bailey, Adriana; Singh, Hansi K. A.; Nusbaumer, Jesse
Abstract: The ability to identify moisture source regions and sinks and to model the transport pathways that link them in simple yet physical ways is critical for understanding climate today and in the past. Using water tagging and isotopic tracer experiments in the Community Earth System Model, this work shows that poleward moisture transport largely follows surfaces of constant moist entropy. The analysis not only provides insight into why distinct zonal bands supply moisture to high‐ and low‐elevation polar sites but also explains why changes in these source regions are inherently linked to changes in temperature and rainout. Moreover, because the geometry, and specifically length, of the moist isentropic surfaces describes how much integrated rainout occurs, the analysis provides a physical framework for interpreting the isotopic composition of water in poleward‐moving air, thus indicating how variations in moisture transport might influence Antarctic ice cores. Key Points: Model experiments with water tags and isotopic tracers reveal poleward moisture transport largely follows surfaces of constant moist entropy Consequently, high‐elevation Antarctic sites receive moisture from more equatorward sources than lower elevation sites The moist isentropic framework suggests shifts in moisture source regions are tightly linked to changes in temperature and rainout